Penerapan Senam Ergonomik pada Lansia Penderita Hipertensi di Desa Kapurancak Kabupaten Boyolali - Ajeng Prameswari; Riyani Wulandari (Calory Journal Medical Laboratory Journal, 2024)
Background: The number of hypertension cases in Boyol ali Regency in 2019 was 26,685 people. Hypertension not only reduces the quality of life, but can also be life-threatening. A lifestyle that is less considered will be one of the factors for hypertension in the elderly. There are two treatments that can be given to people with hypertension, namely pharmacological and non-pharmacological treatments. Non-pharmacological therapy that can be done is physical activity such as exercise, one of which is ergonomic gymnastics. Objective: To describe the results of the implementation of ergonomic gymnastics in elderly people with hypertension in Kapurancak Village, Boyolali Regency. Method: this application with a case study that uses descriptive data collection methods and makes observations on 2 elderly respondents with a history of grade 2 hypertension. The instruments used are observation sheets, and sphygmomanometer. Results: After ergonomic exercise therapy for 20-30 minutes with a frequency of four times in two weeks showed a decrease in blood pressure in both respondents from grade 2 hypertension to grade 1 hypertension. Conclusion: Ergonomic exercise therapy can reduce blood pressure in the elderly.